Analysis of Whole-Genome Sequences for the Prediction of Penicillin Resistance and β-Lactamase Activity in Bacillus anthracis - Gargis, A. S. (mSystems, 2018)
Penicillin (PEN) is a low-cost option for anthrax treatment, but naturally occurring resistance has been reported. β-Lactamase expression (bla1, bla2) in Bacillus anthracis is regulated by a sigma factor (SigP) and its cognate anti-sigma factor (RsiP). Mutations leading to truncation of RsiP were previously described as a basis for PEN resistance. Here, we analyze whole-genome sequencing (WGS) data and compare the chromosomal sigP-bla1 regions from 374 B. anthracis strains to determine the frequency of mutations, identify mutations associated with PEN resistance, and evaluate the usefulness of WGS for predicting PEN resistance. Few (3.5%) strains contained at least 1 of 11 different mutations in sigP, rsiP, or bla1. Nine of these mutations have not been previously associated with PEN resistance. Four strains showed PEN resistance (PEN-R) by conventional broth microdilution, including 1 strain with a novel frameshift in rsiP. One strain that carries the same rsiP frameshift mutation as that found previously in a PEN-R strain showed a PEN-susceptible (PEN-S) phenotype and exhibited decreased bla1 and bla2 transcription. An unexpectedly small colony size, a reduced growth rate, and undetectable β-lactamase activity levels (culture supernatant and cell lysate) were observed in this PEN-S strain. Sequence analysis revealed mutations in genes associated with growth defects that may contribute to this phenotype. While B. anthracis rsiP mutations cannot be exclusively used to predict resistance, four of the five strains with rsiP mutations were PEN-R. Therefore, the B. anthracis sigP-bla1 region is a useful locus for WGS-based PEN resistance prediction, but phenotypic testing remains essential. IMPORTANCE Determination of antimicrobial susceptibility of B. anthracis is essential for the appropriate distribution of antimicrobial agents for postexposure prophylaxis (PEP) and treatment of anthrax. Analysis of WGS data allows for the rapid detection of mutations in antimicrobial resistance (AMR) genes in an isolate, but the presence of a mutation in an AMR gene does not always accurately predict resistance. As mutations in the anti-sigma factor RsiP have been previously associated with high-level penicillin resistance in a limited number of strains, we investigated WGS assemblies from 374 strains to determine the frequency of mutations and performed functional antimicrobial susceptibility testing. Of the five strains that contained mutations in rsiP, only four were PEN-R by functional antimicrobial susceptibility testing. We conclude that while sequence analysis of this region is useful for AMR prediction in B. anthracis, genetic analysis should not be used exclusively and phenotypic susceptibility testing remains essential.